2011
DOI: 10.1007/s11010-011-1180-z
|View full text |Cite
|
Sign up to set email alerts
|

Widdrol activates DNA damage checkpoint through the signaling Chk2–p53–Cdc25A–p21–MCM4 pathway in HT29 cells

Abstract: Widdrol is an odorant compound isolated from Juniperus chinensis. We previously reported that widdrol induces Gap 1 (G1) phase cell cycle arrest and leads to apoptosis in human colon adenocarcinoma HT29 cells. It was also reported that this cell cycle arrest is associated with the induction of checkpoint kinase 2 (Chk2), p53 phosphorylation and cyclin dependent kinase (Cdk) inhibitor p21 expression. In this paper, we investigated the molecular mechanisms of widdrol on the activation of G1 DNA damage checkpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…On the other hand, several different HDACIs have been shown to increase expression of p21 in several different tumor cell lines (42,43). CHEK2 also has been shown to activate p21 (44). In our experiments, we observed a modest induction of p21 upon treatment with CHEK2i and, in agreement with previous reports, a very significant increase in p21 levels when cells were treated with the HDACI AR42.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, several different HDACIs have been shown to increase expression of p21 in several different tumor cell lines (42,43). CHEK2 also has been shown to activate p21 (44). In our experiments, we observed a modest induction of p21 upon treatment with CHEK2i and, in agreement with previous reports, a very significant increase in p21 levels when cells were treated with the HDACI AR42.…”
Section: Discussionsupporting
confidence: 92%
“…To further clarify the molecular mechanisms by which atrazine affects cell cycle and apoptosis in RM1 cells, RT-PCR and western blot analyses were employed to detect the mRNA and protein levels of factors related to cell cycle and apoptosis. The cell cycle has many checkpoints, and p53 and p21 play important roles in cell cycle arrest through the Chk2-p53-Cdc25A-p21-MCM4 signaling pathway, and finally induce G1 cell cycle arrest; overexpression of p21 induces cell cycle arrest (23). In this study, p53 and p21 mRNA and protein levels were downregulated in vitro and in vivo after exposure to atrazine, which indicated that atrazine inhibits cell cycle arrest.…”
Section: Discussionmentioning
confidence: 53%
“…Some odors can induce the phosphorylation of AMP-activated protein kinase (AMPK), leading to cell cycle arrest and apoptosis in a colon cancer cell line [34]. Linalool is capable of mediating antiproliferative effects in melanoma cells [35].…”
Section: Discussionmentioning
confidence: 99%